Efektivitas Parate Eksekusi terhadap Objek Jaminan Hak Tanggungan dalam Perspektif Hukum Positif di Indonesia - Vivilia Agnata Mudi (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Mortgage rights are one of the most common legal forms of collateral used in financing transactions in Indonesia. Parate execution is one of the important innovations in the mortgage rights system. This mechanism allows creditors to sell collateral objects directly without going through court proceedings. This research aims to analyze the legal regulations regarding the execution parate for collateral rights objects in positive law in Indonesia, the effectiveness of the implementation of the execution parate for collateral rights objects in legal practice in Indonesia. The research method uses normative research methods and secondary data. The legal arrangements for execution parate in positive law in Indonesia have been well designed to meet practical needs in debt settlement. The execution parate is one of the important mechanisms in the guarantee legal system in Indonesia, especially in the context of mortgage rights. However, its implementation still faces challenges, especially in terms of protecting debtor rights and potential abuse by creditors.